Time of leafroller infestation and effect on yield in grapes - Lo, P.; Murrell, V.C. (New Zealand Plant Protection, 2000)
Leafroller (Lepidoptera Tortricidae) larvae damage grape bunches directly by feeding on the flowers berries and stalks Damaged berries can become infected by fungi such as Botrytis cinerea that cause diseases leading to further indirect yield losses In a field trial Chardonnay bunches were infested with lightbrown apple moth Epiphyas postvittana larvae at monthly intervals from December to March The greatest losses (12 of the fresh weight at harvest) occurred in bunches infested in December and March In December the main cause of loss of berries was direct feeding damage whereas by March indirect losses to disease outweighed those directly due to larvae Leafroller infestations up to January did not increase disease in bunches above the background level of infection In Hawkes Bay leafrollers have the greatest effect on yields from February onwards when infestation of vines increases greatly and berries become more susceptible to diseases